Association between caffeine consumption and nonalcoholic fatty liver disease: a systemic review and meta-analysis. (January 2016) - Shen, Huafeng; Rodriguez, Andrea C.; Shiani, Ashok; Lipka, Seth; Shahzad, Ghulamullah; Kumar, Ambuj; Mustacchia, Paul
Objectives: Caffeine consumption is reported to be associated with reduced hepatic fibrosis in patients with chronic liver diseases. We performed a systematic review and meta-analysis to assess the association between caffeine consumption and prevalence or hepatic fibrosis of nonalcoholic fatty liver disease (NAFLD) in observational studies. Methods: We searched the literature of all languages from PubMed, EMBASE, and the Cochrane library from 1 January 1980 through 10 January 2015. Total caffeine consumption was defined as the daily intake of caffeine (mg/day) from all caffeine-containing products. Combined and subgroup analyses stratified by study designs, study locations, and type of caffeine intake were performed. Results: Four cross-sectional and two case control studies with a total of 20, 064 subjects were included in the meta-analysis. Among these, three studies with 18, 990 subjects were included in the analysis for prevalence of NAFLD while the other three studies with 1074 subjects were for hepatic fibrosis. Total caffeine consumption (mg/day) was not significantly associated with either the prevalence [pooled mean difference (MD) 2.36; 95% confidence interval (CI) −35.92 to 40.64] or hepatic fibrosis (higher versus lower stages; pooled MD −39.95; 95% CI −132.72 to 52.82) of NAFLD. Subgroup analyses stratified by study designs and locations were also not significant. However, after stratifying by type of caffeine intake, regular coffee caffeine intake (mg/day) was significantly associated with reduced hepatic fibrosis of NAFLD (pooled MD −91.35; 95% CI −139.42 to −43.27; n = 2 studies). Conclusion: Although total caffeine intake is not associated with the prevalence or hepatic fibrosis of NAFLD, regular coffee caffeine consumption may significantly reduce hepatic fibrosis in patients with NAFLD.